2023
DOI: 10.1002/ab.22124
|View full text |Cite
|
Sign up to set email alerts
|

“Consumed by creed”: Obsessive‐compulsive symptoms underpin ideological obsession and support for political violence

Jais Adam‐Troian,
Jocelyn J. Bélanger

Abstract: Radicalization is a process by which individuals are introduced to an ideological belief system that encourages political, religious, or social change through the use of violence. Here we formulate an obsessive‐compulsive disorder (OCD) model of radicalization that links obsessive passion (OP; one of the best predictors of radical intentions) to a larger body of clinical research. The model's central tenet is that individual differences in OCD symptom severity could shape radical intentions via their influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 88 publications
(125 reference statements)
0
8
0
Order By: Relevance
“…This is particularly important if we take into account that previous questions were directly related to Islamic rituals. Adam-Troian and Bélanger (2023) should have taken into account the possibility of such misunderstanding, but as far as we have understood their survey, this was not the case.…”
Section: Radicalization Associated With Ocd Severity or The Four Samplesmentioning
confidence: 96%
See 4 more Smart Citations
“…This is particularly important if we take into account that previous questions were directly related to Islamic rituals. Adam-Troian and Bélanger (2023) should have taken into account the possibility of such misunderstanding, but as far as we have understood their survey, this was not the case.…”
Section: Radicalization Associated With Ocd Severity or The Four Samplesmentioning
confidence: 96%
“…Thus, the use of the Y-BOCS in Adam-Troian and Bélanger's (2023) study cannot lead to the conclusion reported in the full title of their article ("Obsessive-compulsive symptoms underpin ideological obsession and support for political violence"), as it was not meant to measure OCD symptoms in the general population. However, if we assume for the sake of further discussion that the use of the Y-BOCS is, in fact, valid, we can visualize the main result by plotting the reported severity of OCD symptoms against the measure of radicalization to look at the potential relationship.…”
Section: How Not To Measure Obsessive-compulsive Disorder Symptomsmentioning
confidence: 99%
See 3 more Smart Citations